Model for phonetic changes driven by social interactions - Chacoma, Andrés Alberto (2020)
We propose a stochastic model to study phonetic changes as an evolutionary process driven by social interactions between two groups of individuals with different phonological systems. Particularly, we focus on the changes in the place of articulation, inspired by the drift/φ/→/h/observed in some words of Latin root in the Castilian language. In the model, each agent is characterized by a variable of three states, representing the place of articulation used during speech production. In this frame, we propose stochastic rules of interactions among agents which lead to phonetic imitation and consequently to changes in the articulation place. Based on this, we mathematically formalize the model as a problem of population dynamics, derive the equations of evolution in the mean-field approximation, and study the emergence of three nontrivial global states, which can be linked to the pattern of phonetic changes observed in the language of Castile and in other Romance languages.